2003
DOI: 10.1021/jo035279r
|View full text |Cite
|
Sign up to set email alerts
|

NMR Kinetic Investigations of the Photochemical and Thermal Reactions of a Photochromic Chromene

Abstract: The photochromic behavior of 2,2-di(4-fluorophenyl)-6-methoxy-2H-1-chromene has been investigated by 19F NMR spectroscopy. Photocoloration under UV irradiation at low temperature led to the formation of three interconverting photoisomers including two merocyanines and an unprecedented allenyl-phenol isomer. Photobleaching with visible light, which was known to lead to reversion to the initial closed chromene, was shown to increase allenyl-phenol concentration. Thermal relaxation of the preirradiated system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…The enthalpy of activation value agrees with those referred for photochromic compounds (40-120 kJ mol K1 ). 11 The negative value obtained for DS ‡ points to an expected loss of freedom in the recyclization into the original closed form but is difficult to interpret as it includes an unknown contribution from the rearrangement of the solvent (toluene).…”
Section: Activation Energiesmentioning
confidence: 93%
See 2 more Smart Citations
“…The enthalpy of activation value agrees with those referred for photochromic compounds (40-120 kJ mol K1 ). 11 The negative value obtained for DS ‡ points to an expected loss of freedom in the recyclization into the original closed form but is difficult to interpret as it includes an unknown contribution from the rearrangement of the solvent (toluene).…”
Section: Activation Energiesmentioning
confidence: 93%
“…8 According to recent studies these photoproducts can be identified, as the trans-cis (TC) and trans-trans (TT) isomers (Scheme 1) and the fast fading phase, of higher amplitude, can usually be attributed to the TC-isomer. 11 2.3. Mechanistic studies 2.3.1.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…They originate from open merocyanine isomers and are formed via a 1,5-hydrogen shift reaction [2122]. However, these allene intermediates can be avoided by the replacement of hydrogen in the immediate vicinity of the two aryl residues (3-position of 2 H -1-benzopyrans and 2-position of 3 H -naphtho[2,1- b ]pyrans).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years nuclear magnetic resonance (NMR) studies have revealed important details in the photochromic mechanism of this family of compounds, namely on the thermal or photochemical interconversion of the different species and the common involvement of a colourless allenyl-naphthol structure as a key intermediate. [2][3][4] All of these studies were performed in polar solvents, at low temperatures and quite high concentrations (10 À2 M) due to the relatively low instrumental sensitivity. More recently, Maurel et al showed that Surface-Enhanced Resonance Raman Scattering (SERRS) could be used for the study of the photochromic process at ambient temperature and low concentrations (10 À5 M).…”
mentioning
confidence: 99%